Evolution of GOLDEN2-LIKE gene function in C3 and C4 plants - Wang, P; Fouracre, J; Kelly, S; Karki, S; Gowik, U; Aubry, S; Shaw, M; Westhoff, P; Slamet-Loedin, I; Quick, W; Hibberd, J; Langdale, J (2013)
A pair of GOLDEN2-LIKE transcription factors is required for normal chloroplast development in land plant species that encompass the range from bryophytes to angiosperms. In the C4 plant maize, compartmentalized function of the two GLK genes in bundle sheath and mesophyll cells regulates dimorphic chloroplast differentiation, whereas in the C3 plants Physcomitrella patens and Arabidopsis thaliana the genes act redundantly in all photosynthetic cells. To assess whether the cell-specific function of GLK genes is unique to maize, we analyzed gene expression patterns in the C4 monocot Sorghum bicolor and C4 eudicot Cleome gynandra. Compartmentalized expression was observed in S. bicolor, consistent with the development of dimorphic chloroplasts in this species, but not in C. gynandra where bundle sheath and mesophyll chloroplasts are morphologically similar. The generation of single and double mutants demonstrated that GLK genes function redundantly in rice, as in other C3 plants, despite the fact that GLK gene duplication in monocots preceded the speciation of rice, maize and sorghum. Together with phylogenetic analyses of GLK gene sequences, these data have allowed speculation on the evolutionary trajectory of GLK function. Based on current evidence, most species that retain single GLK genes belong to orders that contain only C3 species. We therefore propose that the ancestral state is a single GLK gene, and hypothesize that GLK gene duplication enabled sub-functionalization, which in turn enabled cell-specific function in C4 plants with dimorphic chloroplasts. In this scenario, GLK gene duplication preconditioned the evolution of C4 physiology that is associated with chloroplast dimorphism. © 2012 The Author(s).